2020
DOI: 10.1039/d0ta02334e
|View full text |Cite
|
Sign up to set email alerts
|

P–Fe bond oxygen reduction catalysts toward high-efficiency metal–air batteries and fuel cells

Abstract: An Fe, N, P co-doped carbon framework catalyst (CPFeNPC) with a novel C–P–Fe–Nx–P–C system exhibits superior oxygen reduction reaction (ORR) catalytic performance and shines new light on the real application of metal–N–C catalysts in fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…Table 1 shows that Co−P,N−CNT has excellent activity in acidic media ( E onset =0.981 V, j L =5.6 mA cm −2 ). Very recently, TPP was used to bridge iron ions and ZIF‐8 [50] . The resulted catalyst exhibited high half‐wave potentials in both alkaline and acidic electrolytes ( E 1/2 =0.923 V and 0.791 V, respectively), as well as a high power density of 175 mW cm −2 in a Zn‐air battery.…”
Section: Synthetic Methods and Catalytic Activitymentioning
confidence: 99%
“…Table 1 shows that Co−P,N−CNT has excellent activity in acidic media ( E onset =0.981 V, j L =5.6 mA cm −2 ). Very recently, TPP was used to bridge iron ions and ZIF‐8 [50] . The resulted catalyst exhibited high half‐wave potentials in both alkaline and acidic electrolytes ( E 1/2 =0.923 V and 0.791 V, respectively), as well as a high power density of 175 mW cm −2 in a Zn‐air battery.…”
Section: Synthetic Methods and Catalytic Activitymentioning
confidence: 99%
“…[ 114 ] What's more, our group demonstrated that P coordinated with the Fe–N x site to forming P–Fe–N x exhibits outstanding ORR activity in both acidic and alkaline solutions, as well as high power densities in Zn–air batteries and proton exchange membrane fuel cells test. [ 115 ] Doan‐Nguyen et al reported a solution colloidal synthesis for cobalt phosphide (Co 2 P) nanorods (NRs) with TOPO as the P source. The carbon‐supported Co 2 P NRs not only had comparable activity, but also were remarkably more stable than conventional Pt catalysts for ORR in alkaline solutions (Figure 4c–f).…”
Section: Applications In Energy‐related Electrocatalysismentioning
confidence: 99%
“…DFT calculations revealed that the N and P binary-coordinated iron sites provided suitable energy barrier for oxygen intermediate activation and thus accelerated the reaction kinetics. With triphenylphosphine (PPh 3 ) as the P-containing precursor, Jin and coworkers for the first time reported that P atoms could directly coordinate with the Fe-N x sites and form a C-P-Fe-N x -P-C configuration, which showed an ultrahigh ORR activity with a half-wave potential up to 0.923 V and an ORR Tafel slope of 56 mV dec −1 in alkaline media [ 163 ]. In contrast to directly coordinating with central Fe atoms, the introduction of boron centers in the carbon matrix could also improve the ORR activity of the FeN x sites [ 55 ].…”
Section: Saecs For Oxygen Reduction Reactionsmentioning
confidence: 99%